LA INCONSTITUCIONALIDAD DEL DELITO DE FEMINICIDIO EN EL CÓDIGO PENAL PERUANO - Aranguri Castillo, Anyelo Yonny (2018)
The present investigation is born from a serious context of violence and discrimination against women in Peru, becoming one of the main social problems that we have to face at present, also it is oriented to establish the unconstitutionality of the crime of Feminicide, recently incorporated into the Peruvian penal code (Art.108-B), with the aim of building truly effective public policies. In order to do so, the scopes, definitions, characteristics and functionality of each constitutional principle (legality, culpability and equality) have been delimited in the first place. Subsequently, the nature of the criminal offense was studied, together with its constitutive circumstances, and the whole body of criminal legislation in force was analyzed, including Law No. 30364: "Law to prevent, punish and eradicate violence against women and the members of the family group ''. Once each concept described in the criminal type was developed, it was contrasted with the principles of constitutional court, reaching the conclusion that the crime of feminicide prescribed in our Criminal Code violates the Principle of Legality, Equality and Guilt. Finally, it was examined whether the criminal law could serve as an educational and social change instrument, concluding that deficiencies, exclusions or discriminations that occur in society can not be compensated for by higher penal intervention fees. Criminal law is not and will not be self-sufficient in this sense, it is necessary, due to the multidimensional nature of this problem, for the state to intervene in all spheres of state organization; health, economy, politics, social development and above all it must influence public education, because this is key for the development of Peruvian people who respect human rights and are aware that in the eyes of justice we are all equal, regardless of sex.